(In)stability of symbiotic vortex-bright soliton in holographic immiscible binary superfluids - Yu-Ping An; Li Li (Journal of High Energy Physics)
Abstract Symbiotic vortex-bright soliton structures with non-trivial topological charge in one component are found to be robust in immiscibel two-component superfluids, due to the effective potential created by a stable vortex in the other component. We explore the properties of symbiotic vortex-bright soliton in strongly coupled binary superfluids by holography, which naturally incorporates finite temperature effect and dissipation. We show the dependence of the configuration on various parameters, including the winding number, temperature and inter-component coupling. We then study the (in)stability of symbiotic vortex-bright soliton by both the linear approach via quasi-normal modes and the full non-linear numerical simulation. Rich dynamics are found for the splitting patterns and dynamical transitions. Moreover, for giant symbiotic vortex-bright soliton structures with large winding numbers, the vortex splitting instability might be rooted in the Kelvin-Helmholtz instability. We also show that the second component in the vortex core could act as a stabilizer so as to suppress or even prevent vortex splitting instability. Such stabilization mechanism opens possibility for vortices with smaller winding number to merge into vortices with larger winding number, which is confirmed for the first time in our simulation.